Music Performance on 19th-Century Sukuma-Nyamwezi Caravans to the Swahili Coast - Gunderson, Frank (International Library of African Music, 2008)
This article examines the utility and significance of music performed on 19th- century caravans journeying between the inland East African Sukuma-Nyamwezi and interlacustrine regions, and the Swahili coast. This research will show that through music and "soundscape production”, Sukuma-Nymawezi porters or bapagati maintained their identity and dignity albeit intermittently, in spite of the rigors sustained on the long march.
Keywords: African Music